Information asset as property: a legal perspective - Zulhuda, Sonny; Ansari, Abdul Haseeb (Springer, Singapore, 2018)
‘Information asset’ has not been perceived only as a jargon of the information age we are living today. Rather, it has increasingly become the reality, where people and society attach more values on business information and information system. The contemporary ‘information age’ is, therefore, not merely about a change of gadgets, but more so about a change of a whole environment. It is an arena where information becomes the main asset of business and the most valuable property of its owner.